Analisis Peluang dan Ancaman Perdagangan Produk Elektronik Konsumen serta Strategi Peningkatan Daya Saing: Studi Kasus Indonesia dan Amerika Serikat dalam Kerangka APEC - Siti Nuraini (Jurnal Ekonomi dan Bisnis Digital, 2025)
The trade of consumer electronics between Indonesia and the United States offers significant opportunities for both countries to leverage their respective potentials. Indonesia has a comparative advantage in electronic production, while the United States is a primary market with high demand for electronic products. Within the framework of multilateral economic cooperation under APEC, both countries can strengthen their trade relations by reducing tariff barriers and facilitating smoother trade flows. However, Indonesia faces significant challenges, including dependency on component imports, fluctuations in raw material prices, and intense competition from other countries such as China and South Korea. To maximize market potential, Indonesia must focus on technology development, increasing production capacity, and simplifying trade regulations and policies. This study aims to analyze the opportunities and threats in consumer electronics trade, as well as provide strategic recommendations to enhance Indonesia's competitiveness in the global market.